RNA interference-based functional knockdown of the voltage-gated potassium channel Kv7.2 in dorsal root ganglion neurons after in vitro and in vivo gene transfer by adeno-associated virus vectors. Issue 1 (January 2018) - Valdor, Markus; Wagner, Anke; Röhrs, Viola; Berg, Johanna; Fechner, Henry; Schröder, Wolfgang; Tzschentke, Thomas M; Bahrenberg, Gregor; Christoph, Thomas; Kurreck, Jens
Activation of the neuronal potassium channel Kv7.2 encoded by the KCNQ2 gene has recently been shown to be an attractive mechanism to inhibit nociceptive transmission. However, potent, selective, and clinically proven activators of Kv7.2/Kv7.3 currents with analgesic properties are still lacking. An important prerequisite for the development of new drugs is a model to test the selectivity of novel agonists by abrogating Kv7.2/Kv7.3 function. Since constitutive knockout mice are not viable, we developed a model based on RNA interference-mediated silencing of KCNQ2 . By delivery of a KCNQ2 -specific short hairpin RNA with adeno-associated virus vectors, we completely abolished the activity of the specific Kv7.2/Kv7.3-opener ICA-27243 in rat sensory neurons. Results obtained in the silencing experiments were consistent between freshly prepared and cryopreserved dorsal root ganglion neurons, as well as in dorsal root ganglion neurons dissociated and cultured after in vivo administration of the silencing vector by intrathecal injections into rats. Interestingly, the tested associated virus serotypes substantially differed with respect to their transduction capability in cultured neuronal cell lines and primary dorsal root ganglion neurons and the in vivo transfer of transgenes by intrathecal injection of associated virus vectors. However, our study provides the proof-of-concept that RNA interference-mediated silencing of KCNQ2 is a suitable approach to create an ex vivo model for testing the specificity of novel Kv7.2/Kv7.3 agonists.